2011
DOI: 10.1111/j.1365-2109.2011.02949.x
|View full text |Cite
|
Sign up to set email alerts
|

Experimental assessment of the utility of visible implant elastomer tags in a stock improvement programme for giant freshwater prawn (Macrobrachium rosenbergii) in Vietnam

Abstract: An important requirement of many breeding programmes for aquaculture species is the ability to identify organisms individually or at least by family. While a variety of external and internal tagging methods have been developed that can provide efficient identifications systems, most have specific drawbacks. The present study assessed the efficiency of an internal tagging method that can be applied to family selection programmes in crustacean species. Experiments were conducted to test the efficacy of applying … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(8 citation statements)
references
References 27 publications
0
8
0
Order By: Relevance
“…Subcutaneous ink or acrylic paint injection has also been successful for long-lasting readability in aquatic animals (Herbinger et al, 1990), as have visible implant (VI) elastomer or alphanumeric tags (NMT, WA, USA), which have been reported to be successfully used with small aquatic animals [e.g. shrimp (Brown et al, 2003;Dinh et al, 2012;Imbert et al, 2007;Jensen et al, 2008;Pillai et al, 2009)]. In our experience, however, none of these tagging methods were successful with zebrafish: paint tags faded away and VI tags were lost after 2-3weeks.…”
Section: Introductionmentioning
confidence: 99%
“…Subcutaneous ink or acrylic paint injection has also been successful for long-lasting readability in aquatic animals (Herbinger et al, 1990), as have visible implant (VI) elastomer or alphanumeric tags (NMT, WA, USA), which have been reported to be successfully used with small aquatic animals [e.g. shrimp (Brown et al, 2003;Dinh et al, 2012;Imbert et al, 2007;Jensen et al, 2008;Pillai et al, 2009)]. In our experience, however, none of these tagging methods were successful with zebrafish: paint tags faded away and VI tags were lost after 2-3weeks.…”
Section: Introductionmentioning
confidence: 99%
“…Size was more highly variable among our lobsters, ranging from 7 to 15 mm CL, so it may be that the occurrence of relatively small lobsters in our trial increased the incidence of tag loss; smaller animal size limits the volume of VIE that can be implanted which can affect tag retention and detectability (Dinh et al . ). The analysis of tag retention against carapace length was shown to be non‐significant but this relationship may have shown greater influence had the animal size groups contained a more even distribution of lobster numbers (CL size groups, from smallest to largest, included 83, 126, 38 and seven lobsters).…”
Section: Discussionmentioning
confidence: 97%
“…Previous studies have already shown VIE tags to be an effective tool for marking juvenile crustaceans of very small body size (e.g. 2 g Giant freshwater prawns – Dinh, Coman, Hurwood & Mather ), and several studies have assessed VIE tags in cultured European lobster juveniles. Of 25 hatchery‐reared juvenile H. gammarus tagged with VIE at approximately 1‐year old by Uglem et al .…”
Section: Introductionmentioning
confidence: 99%
“…First, individuals require physical tagging, which is time consuming and can be expensive. In crustacean aquaculture, furthermore, individuals moult as they grow, thereby discarding externally applied tags making assignment back to their respective strains problematic (but see Dinh, Coman, Hurwood & Mather 2012;Pillai et al 2011). Problems associated with tagging have been overcome in some cases, e.g.…”
Section: Discussionmentioning
confidence: 99%